Road Drift. (3rd October 2018) - Whybrow, Nicolas
Abstract : "Road Drift" has been conceived as a counterpart to "Road Rumour: Ground Plans for the Sky Blue City" which appeared in Performance Research journal's centenary edition (23.4/5, 2018). This fictional piece presented an anonymous document – a text + image montage – entitled 'Bare City: We'll Live and Die in These Towns' which envisaged the fantasy of Coventry's ring-road being converted into a traffic-free pedestrian eco-zone, incorporating pop-up facilities, open markets, artworks etc. – above all somewhere that would not only lure suburban citizens into the centre but encourage them to interact and relish being there, and therefore linger (in the best tradition of Jan Gehl). The overall aim of these two complementary items is, first, to track urban entropies and, second, galvanise urban change. Where "Road Rumour" sought, as a fictional projection into the future, to address the latter, offering a utopian possibility in the 'subjunctive mood', "Road Drift" will concern itself more with the former, presenting a dystopian view in the 'disjunctive mood'. It too bases itself on the discovery of an anonymous document, this time entitled 'Dysjunction: these Towns will Live and Die'. It is a mapping that seeks to document a residual temporal drift, confronting the reality of the present – what the then-becoming post-war city has become – with the recent past: what future or 'tomorrow' was being dreamed of, or up, for the becoming city in the heady era of 1950s and 1960s civic planning and rebuilding. Focusing on one junction in particular, the montage records a drift but not that of the pedestrian or, indeed, Situationist "small group of adepts" in the city; rather it is the drift of a road in time and space and, by figurative extension, the drift of the city itself.